Clinical and Biological Factors Affecting Left Ventricular End-Diastolic Pressure in ST-Segment Elevation Myocardial Infarction - Sadiq, Muhammad Wajid; Siddique, Muhammad Bilal; Farhan, Shaheer; Ahmed, Iftikhar; Haider, Riaz; Shahzad, Malik Muhammad Khurram (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the clinical & biological factors affecting Left Ventricular End Diastolic Pressure(LVEDP) in ST-Segment Elevation Myocardial Infarction (STEMI) patients undergoing coronary angiography followed by Primary Percutaneous Coronary Intervention(PPCI). Study Design: Quasi-Experimental study. Place and Duration of Study: Armed Forces Institute of Cardiology/National Institute of Heart Diseases, Rawalpindi Pakistan, from Feb-Aug 2024. Methodology: Ninety-six STEMI patients regardless of gender were enrolled through consecutive sampling. Baseline variables like Hs-Trop I, BMI, Ejection Fraction, Mean Arterial Pressure, and Killip Class were noted upon patient arrival at emergency room. LVEDP was measured using pigtail catheter during coronary-angiography and patients were classified non-randomly in two Groups: LVEDP<16mmHg (Group-A) and ≥16mmHg (Group-B). Coronary artery disease severity was assessed using the Gensini score. Clinical parameters and biological parameters were compared between Groups. Results: Ninety-six patients [males: 66(68.8%), females: 30(31.2%)] with composite mean age 63.26±7.99 years were enrolled in study. For LVEDP, 51(53.1%) patients had values <16mmHg, while 45(46.9%) had LVEDP≥16mmHg. BMI was significantly higher in Group-B [30.00(24.00-34.00) kg/m² vs 24.00(22.00-26.00) kg/m²; p<0.001] and all the patients classified as Killip class III/IV had LVEDP≥16 mmHg (p<0.001). There was significant difference in mean values of Gensini score, EF, NT-proBNP, Hs Trop-I, MAP, TG and eGFR with comparatively higher mean values in Group-B patients except EF and eGFR (p<0.01). Correlation was significant between LVEDP and aforementioned clinical parameters except TRG (p<0.001). Conclusion: LVEDP is strongly associated with higher BMI, advanced Killip class, and increased coronary artery severity. It also correlates with elevated cardiac biomarkers and reduced ejection fraction,..